Laba/Rugi Investasi Emas Derivatif Broker: Modal dan Biaya Transaksi. - Nelli Novyarni; Elizabeth Yuswantoro; Reni Harni (Jurnal Manajemen, 2022)
This study aims to determine Profit or Loss of Gold Derivative Investments: Capital and Transaction Costs. This research uses a quantitative approach, which is measured by using the SPSS version 25 application. The population of this research is gold derivative investors registered at PT. Trijaya Pratama Futures in 2021. The sample was determined based on the convenience sampling method, with a total of 30 gold derivative investors. The statistical test technique used is partial and multiple linear analysis. The results of the study prove that (1) Capital has an effect on Profit and Loss of Derivative Gold Investment and (2) Transaction Costs affect the Profit and Loss of Derivative Gold Investment.